Inter-professional ethical values in Iranian aged care: a qualitative study - Reza Hosseinabadi; Yadollah Abolfathi Momtaz; Farahnaz Mohammdi Shahboulaghi; Abbas Abbaszadeh; Ahmad Ali Akbari Kamrani; Yadollah Pournia (Medicinski glasnik, 2019)
Aim: Ethical values are the basis of the behaviour and performance of professional care staff. This study aimed to identify inter-professional ethical values in aged care. Methods: This qualitative thematic content analysis study was conducted in Khorramabad, Iran, from September 2018 to June 2109, and 36 core members of the aged care team (including 24 nurses, 5 physicians, 3 physiotherapists, and 4 social workers) were selected through the purposive sampling method and interviewed in depth. The data were analysed using the directed content analysis and the method of Zhang and Wildemuth. Results: Four main themes of providing professional care, preserving the integrity of the aged, observing the dignity of the aged, establishing human relationship, along with 21 subthemes were extracted as ethical values in aged care. Conclusion: The results of this study indicate that providing ethical aged care is influenced by the specific conditions of this age group. In addition to general ethical values such as providing professional care, providing ethical aged care is based on ethical values such as promoting social interaction, promoting peace and comfort, preserving and promoting independence, and autonomy in aged care. Promoting collaborative care and paying more attention to the human dimensions of communication and interaction were other emphasized values.
Keywords: elderly; ethical aspects; Islamic Republic of Iran; medical ethics; nursing ethics